Young, small-scale surface features in Meridiani Planum, Mars: A possible signature of recent transient liquid and gas emissions. (August 2018) - Horne, David J.
Abstract: Enigmatic small-scale (<1 m) depositional and erosional features found in basaltic sands partly covering bedrock exposures, imaged at several locations in the equatorial Meridiani Planum region by the Mars Exploration Rover Opportunity, may be evidence of previously unrecognized, geologically young (or even contemporary) Martian surface processes. Leveed fissures appear to have formed by venting from beneath; possible explanations include aeolian blowholes near crater margins, volcanic fumarole activity, or gas/vapour escape resulting from the decomposition of small pockets of ground ice, methane clathrates or hydrated sulphate minerals. Some leveed fissures cross-cut and are therefore younger than aeolian ripples thought to have last been active c. 50, 000 years ago. Erosional gutters are sharply defined and fresh-looking, internally terraced, sometimes are deeper near one end, and in one case seem to give way to small depositional fans downslope; they have the appearance of having been formed by liquid flow rather than by wind erosion. There is evidence elsewhere that contemporary ground-ice thaw and consequent transient surface run-off may occur occasionally under present conditions at low, near-equatorial latitudes on Mars; short-lived (even for just a few minutes) meltwater emission and flow at the surface could form gutters before evaporating. Further possibilities are the decomposition of buried pockets of methane clathrates (which theoretical considerations suggest might be present and stable even in equatorial regions) giving rise to both methane gas venting and transient surface water, or the release of liquid brines by decomposition of hydrated magnesium sulphate minerals or deliquescence of perchlorates. Dry granular flow mechanisms proposed as explanations for Recurring Slope Lineae seem inadequate to explain the morphologies of leveed fissures and gutters. Highlights: Enigmatic small surface features in equatorial Mars merit further investigation. Leveed fissures may have been constructed by venting of gas from beneath. Gutters may have been eroded by short-lived liquid flow on the surface. Leveed fissures are less than 50, 000 years old and possibly formed very recently. Localised ground ice melting or sublimation may form both types of feature.